Added Value of Intangibles for Organizational Innovation - Luoma-acho, Vilma; Vos, Marita; Lappalainen, Raimo; Lämsä, Anna; Uusitalo, Outi; Maaranen, Petri; Koski, Aleksi (Human Technology, 2012)
The purpose of this paper is to present the theoretical basis for a measurement and improvement system that will help organizations create a more innovative climate. The role of intangible assets in contributing to organizational innovativeness is clarified within six hypotheses on the basis of a cross-disciplinary literature review combining studies from psychology, human resources management, communication, information technology, and marketing. These factors range from the individual level to interaction with the environment surrounding the organization, and involve (a) individual psychological flexibility, (b) institutional and interpersonal trust, (c) diverse human resources, (d) strategic transformational leadership, (e) agile information and communication technology systems, and (f) coproduction of the brand with customers. The critical factors point out areas for organizational innovation, and we advocate a cross-disciplinary approach to ensure that diverse aspects of organizational life are considered. These hypotheses require testing in order to assist organizations in improving their innovativeness.